Generation of total angular momentum eigenstates in remote qubits - Maser, Andreas; Schilling, Uwe; Bastin, T.; Solano, E.; Thiel, Christoph; von Zanthier, Joachim (Physical Review A, 2009)
We propose a scheme enabling the universal coupling of angular momentum of N remote noninteracting qubits using linear optical tools only. Our system consists of N single-photon emitters in a Lambda configuration that are entangled among their long-lived ground-state qubits through suitably designed measurements of the emitted photons. In this manner, we present an experimentally feasible algorithm that is able to generate any of the 2(N) symmetric and nonsymmetric total angular momentum eigenstates spanning the Hilbert space of the N-qubit compoun
Keywords: eigenvalues and eigenfunctions; ground states; Hilbert spaces; quantum computing; quantum entanglement; quantum optics

Heralded entanglement of arbitrary degree in remote qubits - Schilling, Uwe; Thiel, Christoph; Solano, E.; Bastin, T.; von Zanthier, Joachim (Physical Review A, 2009)
Incoherent scattering of photons off two remote atoms with a Lambda-level structure is used as a basic Young-type interferometer to herald long-lived entanglement of an arbitrary degree. The degree of entanglement, as measured by the concurrence, is found to be tunable by two easily accessible experimental parameters. Fixing one of them to certain values unveils an analog to the Malus' law. An estimate of the variation in the degree of entanglement due to uncertainties in an experimental realization is give

Measuring arbitrary-order coherences: Tomography of single-mode multiphoton polarization-entangled states - Schilling, Uwe; von Zanthier, Joachim; Agarwal, G. S. (Physical Review A, 2010)
A scheme is discussed for measuring Nth-order coherences of two orthogonally polarized light fields in a single spatial mode at very limited experimental cost. To implement the scheme, the only measurements needed are the Nth-order intensity moments after the light beam has passed through two quarter-wave plates, one half-wave plate, and a polarizing beam splitter for specific settings of the wave plates. It is shown that this method can be applied for arbitrarily large N. A set of explicit values is given for the settings of the wave plates, constituting an optimal measurement of the Nth-order coherences for any N. For Fock states the method introduced here corresponds to a full state tomography. Applications of the scheme to systems other than polarization optics are discusse

Phase-dependent which-way information - Schilling, Uwe; von Zanthier, Joachim (Physics Letters A, 2012)
We introduce an observable for reading out a which-way detector in a Young-type interferometer whose eigenstates either contain full which-way information or none at all. We calculate the which-way knowledge kappa that can be retrieved from this observable and find that kappa depends on the phase difference delta that the interfering quantum object accumulates on its passage through the interferometer. It turns out that for certain phase shifts kappa(delta) equals one, independent of the visibility of the interference pattern. In addition, within a certain range of phase shifts kappa(delta) can be larger than the which-way information obtained from the observable recognized to provide optimal which-way information on average. (C) 2012 Elsevier BM. All rights reserved.
Keywords: Wave-particle duality; Which-way information; Quantum eraser; Micromaser

Simulating the coupling of angular momenta in distant matter qubits - Ammon, C.; Maser, Andreas; Schilling, Uwe; Bastin, T.; von Zanthier, Joachim (Physical Review A, 2012)
We present a mathematical proof of the algorithm allowing one to generate all-symmetric and nonsymmetric-total angular momentum eigenstates in remote matter qubits by projective measurements, proposed in Maser et al. [Phys. Rev. A 79, 033833 (2009)]. By deriving a recursion formula for the algorithm we show that the generated states are equal to the total angular momentum eigenstates obtained via the usual quantum-mechanical coupling of angular momenta. In this way we demonstrate that the algorithm is able to simulate the coupling of N spin-1/2 systems, and to implement the required Clebsch-Gordan coefficients, even though the particles never directly interact with each othe

Versatile source of polarization-entangled photons - Maser, Andreas; Wiegner, Ralph; Schilling, Uwe; Thiel, Christoph; von Zanthier, Joachim (Physical Review A, 2010)
We propose a method for the generation of a large variety of entangled states, encoded in the polarization degrees of freedom of N photons, within the same experimental setup. Starting with uncorrelated photons, emitted from N arbitrary single-photon sources, and using linear optical tools only, we demonstrate the creation of all symmetric states (e. g., GHZ and W states), as well as all symmetric and nonsymmetric total angular momentum eigenstates of the N-qubit compoun